Grit and Intention: Why Do Learners Complete MOOCs? - Wang, Yuan; Baker, Ryan (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2018)
In recent years there has been considerable interest in how many learners complete MOOCs, and what factors during usage can predict completion. Others, however, have argued that many learners never intend to complete MOOCs, and take MOOCs for other reasons. There has been qualitative research into why learners take MOOCs, but the link between learner goals and completion has not been fully established. In this paper, we study the relationship between learner intention to complete a MOOC and their actual completion status. We compare that relationship to the degree to which MOOC completion is predicted by other domain-general motivational factors such as grit, goal orientation, academic efficacy, and the need for cognition. We find that grit and goal orientation are associated with course completion, with grit predicting course completion independently from intention to complete, and with comparable strength.